2014
DOI: 10.1080/00224499.2014.910290
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Religiosity on the Sexual Risk Behaviors of Young Men Who Have Sex With Men

Abstract: Young men who have sex with men (YMSM), particularly Black YMSM, bear a disproportionate burden of new HIV infections in the U.S. Several studies support the positive and protective role of religion in health and the prevention of morbidity and mortality. However, little empirical research has been conducted looking at religion with the context of YMSM and HIV prevention. We examined the impact of religious attendance and faithfulness on sexual risk among a community-based sample of 450 YMSM in Chicago ages 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Prior work of racially diverse YBMSM suggests faithfulness and frequent formal religious attendance was associated with less condomless anal intercourse with male partners [90]. …”
Section: Figurementioning
confidence: 99%
“…Prior work of racially diverse YBMSM suggests faithfulness and frequent formal religious attendance was associated with less condomless anal intercourse with male partners [90]. …”
Section: Figurementioning
confidence: 99%
“…At the individual level, sexual identity development and perceptions of first same-sex sexual experiences may be uniquely influenced by body image (Cash, Maikkula, & Yamamiya, 2004; Wilton, 2009) and religiosity (Garofalo et al, 2014; Higgins et al, 2010; Regnerus, 2007), in addition to age at first sex, which was described above.…”
Section: Introductionmentioning
confidence: 98%
“…One recent study among young BMSM in Chicago found religiosity and frequent religious attendance to be associated with fewer instances of unprotected anal sex(Garofalo et al, 2014). Based on what they describe as the “historical tension between certain religious doctrine and sexual minorities” (p.9), study authors called for “qualitative data about the experiences of religious practices and beliefs among YMSM” (Garofalo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One recent study among young BMSM in Chicago found religiosity and frequent religious attendance to be associated with fewer instances of unprotected anal sex(Garofalo et al, 2014). Based on what they describe as the “historical tension between certain religious doctrine and sexual minorities” (p.9), study authors called for “qualitative data about the experiences of religious practices and beliefs among YMSM” (Garofalo et al, 2014). Other research has described the homophobia and the HIV-related stigma that BMSM face in religious institutions (Balaji et al, 2012; Valera & Taylor, 2011; Wilson, Wittlin, Muñoz-Laboy, & Parker, 2011) and the family (Balaji et al, 2012; Hussen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%